2005
DOI: 10.1002/hbm.20089
|View full text |Cite
|
Sign up to set email alerts
|

Difference in somatosensory evoked fields elicited by mechanical and electrical stimulations: Elucidation of the human homunculus by a noninvasive method

Abstract: We recently recorded somatosensory evoked fields (SEFs) elicited by compressing the glabrous skin of the finger and decompressing it by using a photosensor trigger. In that study, the equivalent current dipoles (ECDs) for these evoked fields appeared to be physiologically similar to the ECDs of P30m in median nerve stimulation. We sought to determine the relations of evoked fields elicited by mechanically stimulating the glabrous skin of the great toe and those of electrically produced P40m. We studied SEFs el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Our results objectively confirmed the findings of previous studies [6,7], that cortical cSI responses could be evoked not only by compressive stimuli but also by decompressive stimuli in all subjects. However, in our study, dipole strength of decompressive-cSI responses was smaller than that of compressive stimuli, since compression was approximately 4 times as fast as decompression (39.4±0.6cm/s and 10.1±1.2cm/s, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results objectively confirmed the findings of previous studies [6,7], that cortical cSI responses could be evoked not only by compressive stimuli but also by decompressive stimuli in all subjects. However, in our study, dipole strength of decompressive-cSI responses was smaller than that of compressive stimuli, since compression was approximately 4 times as fast as decompression (39.4±0.6cm/s and 10.1±1.2cm/s, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…One possible explanation is that the SII responses were related to stimulus strength, in terms of faster stimulus being a stronger stimulus and vice versa, since compression were approximately 4 times as strong (fast) as decompression. However, subjectively strong (fast) decompressive stimuli could not evoke SII responses [6,7]. In addition, despite the difference in nature of the stimuli, weak electrical stimuli (at twice the sensory threshold) could evoke SII responses [21].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous MEG studies have shown that the somatosensory information processing involves activation in primary and secondary somatosensory cortices (Forss et al, 1994;Hari and Forss, 1999;Karhu and Tesche, 1999;Kakigi et al, 2000;Hoechstetter et al, 2001). Most studies, however, used electrical stimulation of peripheral nerves to activate a broad range of cutaneous receptors or tactile stimulation to activate mainly slowly adapting mechanoreceptors (Forss et al, 1994;Rossini et al, 1996;Jousmäki, 2000;Inoue et al, 2005;Hautasaari et al, 2019). Much less is known about brain responses activated by rapidly adapting mechanoreceptors, i.e., Meissner and Pacinian corpuscles.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found that human mechanical touch stimuli induce somatosensory cortical responses not only when glabrous skin is compressed but also when it is decompressed in the index finger [Inoue et al, 2005;Shirai et al, 2004]. It is thought that the somatosensory cortical responses were evoked not only by action potentials from skin receptors such as Pacinian corpuscles but also by offset cortical responses (off-responses) when glabrous skin is decompressed [Crevits et al, 1982;Hari et al, 1987;Noda et al, 1998;Pantev et al, 1996;Wakai et al, 2007].…”
Section: Introductionmentioning
confidence: 99%